Animation in the video format as a technology for the promotion of breastfeeding (Research, Society and Development, 2020)
For the pregnant woman to decide to breastfeed, clarification is needed on the importance and benefits of breastfeeding.  This study aimed to report the process of creating a technology on the importance of breastfeeding, through the action research methodology. It is important to emphasize the importance of the theme and the need for health promotion aimed at users through playful means that facilitate understanding of the reality of the place. The population, in general, requires and needs a differentiated education, through innovations and technological advances. The video aims to demonstrate, in a fast, lively, clear and simple way, the importance of breastfeeding.